Characterization of DvSSJ1 transcripts targeting the smooth septate junction (SSJ) of western corn rootworm (Diabrotica virgifera virgifera) - Xu Hu (Nature Portfolio, 2020)
Abstract Transgenic maize plants expressing dsRNA targeting western corn rootworm (WCR, Diabrotica virgifera virgifera) DvSSJ1 mRNA, a Drosophila snakeskin (ssk) ortholog, show insecticidal activity and significant plant protection from WCR damage. The gene encodes a membrane protein associated with the smooth sepate junction (SSJ) which is required for intestinal barrier function. To understand the active RNA form that leads to the mortality of WCR larvae by DvSSJ1 RNA interference (RNAi), we characterized transgenic plants expressing DvSSJ1 RNA transcripts targeting WCR DvSSJ1 mRNA. The expression of the silencing cassette results in the full-length transcript of 901 nucleotides containing a 210 bp inverted fragment of the DvSSJ1 gene, the formation of a double-stranded RNA (dsRNA) transcript and siRNAs in transgenic plants. Our artificial diet-feeding study indicates that dsRNAs greater than or equal to approximately 60 base-pairs (bp) are required for DvSSJ1 insecticidal activity. Impact of specificity of dsRNA targeting DvSSJ1 mRNA on insecticidal activities was also evaluated in diet bioassay, which showed a single nucleotide mutation can have a significant impact or abolish diet activities against WCR. These results provide insights as to the functional forms of plant-delivered dsRNA for the protection of transgenic maize from WCR feeding damage and information contributing to the risk assessment of transgenic maize expressing insecticidal dsRNA.